Health profile and quality of life of elderly with hypertension - Gabriela Freire de Almeida Vitorino; Mayara Inácio de Oliveira; Hirla Vanessa Soares de Araújo; Rebeka Maria de Oliveira Belo; Thaisa Remigio Figueirêdo; Simone Maria Muniz da Silva Bezerra (Rev Rene)
Objective: to evaluate the quality of life of hypertensive elderly women in the Family Health Strategy. Method: cross-sectional, descriptive and quantitative study that evaluated 60 hypertensive older women using the tool World Health Organization Quality of Life with 26 items divided into four domains: social relations, psychological, physical and environment. Results: regarding the quality of life in all domains, except the psychological domain, the quality of life was considered regular. The psychological domain demonstrated a quality of life that needs to improve. Some questions are presented as unsatisfactory, such as the items: pain and discomfort, dependence on antihypertensive medications, negative feelings, lack of health care and recreation. Conclusion: understanding the health profile and the quality of life of hypertensive elderly women allows better knowledge about them and their adaptation to the condition imposed by the disease, offering support for planning care strategies and health education interventions.